From idea to systems solution: enhancing access to primary care in Malawi - L. van Niekerk; N. Fosiko; A. Likaka; C. P. Blauvelt; B. Msiska; L. Manderson (BMC, 2023)
Abstract Malawi, like many other countries, faces challenges in providing accessible, affordable, and quality health services to all people. The Malawian policy framework recognizes the value of communities and citizens, as co-creators of health and leaders of localized and innovative initiatives, such as social innovations. Social innovations involve and include communities and citizens, as well as bring about changes in the institutions responsible for care delivery. In this article, we describe the institutionalization process of a citizen-initiated primary care social innovation, named Chipatala Cha Pa Foni, focused on extending access to health information and appropriate service-seeking behavior. An interdisciplinary multi-method qualitative case study design was adopted, drawing on data collected from key informant interviews, observations, and documents over an 18-month period. A composite social innovation framework, informed by institutional theory and positive organizational scholarship, guided the thematic content analysis. Institutional-level changes were analyzed in five key dimensions as well as the role of actors, operating as institutional entrepreneurs, in this process. A subset of actors matched the definition of operating as Institutional Entrepreneurs. They worked in close collaboration to bring about changes in five institutional dimensions: roles, resource flows, authority flows, social identities and meanings. We highlight the changing role of nurses; redistribution and decentralization of health information; shared decision-making, and greater integration of different technical service areas. From this study, the social innovation brought about key institutional and socio-cultural changes in the Malawi health system. These changes supported strengthening the system's integrity for achieving Universal Health Coverage by unlocking and cultivating dormant human-based resources. As a fully institutionalized social innovation, Chipatala Cha Pa Foni has enhanced access to primary care and especially as part of the Covid-19 response.